2010
DOI: 10.1088/0022-3727/43/44/445202
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional modelling of DBDs in Ne–Xe mixtures for excimer lamps

Abstract: Dielectric barrier discharges (DBDs) are a promising technology for high-intensity sources of specific UV and VUV radiation. In this work, the microdischarge dynamics in DBDs for Ne−Xe mixtures under the close conditions of excimer lamp working has been investigated. The computer model including the cathode fall, the positive column and the dielectric is composed of two coupled sub-models. The first submodel describes the electrical properties of the discharge and is based on a fluid, two-moments description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The transport coefficients and the electronic collision frequencies, which depend on the reduced electric field (E/N), are precalculated and tabulated by solving the steady state, homogeneous electron Boltzmann equation, using BOLSIG solver [26]. It is worth noting that the bibliographic research on the electronic reaction rates shows that most of references are long-established, but they constitute the basis of the set of models used for description of plasma display panels [27], excimer lamps and lasers [10,14,16,[28][29][30].…”
Section: Numerical Modelmentioning
confidence: 99%
“…The transport coefficients and the electronic collision frequencies, which depend on the reduced electric field (E/N), are precalculated and tabulated by solving the steady state, homogeneous electron Boltzmann equation, using BOLSIG solver [26]. It is worth noting that the bibliographic research on the electronic reaction rates shows that most of references are long-established, but they constitute the basis of the set of models used for description of plasma display panels [27], excimer lamps and lasers [10,14,16,[28][29][30].…”
Section: Numerical Modelmentioning
confidence: 99%
“…However, the kinetic processes in the plasma responsible for the enhanced lamp performance and increased efficiency are not well understood and the principal disadvantage of excimer DBD discharge is especially their low efficiency. Furthermore in order to optimize the discharge luminance efficiency, several experimental, theoretical and detailed computer-modeling studies of the plasma kinetics in pulse-excited DBDs have been realized in the last decade [17][18][19][20][21][22][26][27][28][29][30][31][32][33][34][35][36][37][38]. It has been shown that the efficiency of excimer lamp can be increased up to 60% by employing a fast rise-time and a short pulsed voltage excitation [21,24,37,39].…”
Section: Introductionmentioning
confidence: 99%